Dakwah Digital dan Persepsi Gen-Z pada Podcast Husein Ja'far - Mochammad Ghilman Waliyyana; Malki Ahmad Nasir; Ahmad Muttaqin (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study aims to describe the form of da'wah messages about religious tolerance delivered through Husein Ja'far's podcast and to analyze the form of Generation Z's perception of religious tolerance da'wah heard through Husein Ja'Far's podcast. This research is a qualitative study with a descriptive approach that aims to describe the influence of digital da'wah on Generation Z's religious perceptions. The data collection techniques uses literature study techniques, observation, and interviews. The results showed that Husein Ja'far's odcast succeeded in becoming an effective digital da'wah media to convey messages of religious tolerance. The use of digital platforms familiar to Generation Z, such as YouTube, supports the spread of inclusive Islamic values. The delivery method used is casual but meaningful, thus attracting the attention of young listeners. This research is expected to be a reference for da'wah actors so that the da'wah approach is more attractive and in accordance with the needs of adolescents in increasing religious awareness and participation. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan bentuk pesan-pesan dakwah tentang toleransi beragama yang disampaikan melalui podcast Husein Ja’far dan untuk menganalisis bentuk persepsi Generasi Z tentang dakwah toleransi beragama yang didengar melalui podcast Husein Ja’Far. Dalam penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif yang bertujuan untuk menggambarkan pengaruh dakwah digital terhadap persepsi keagamaan Generasi Z. Teknik pengumpulan data menggunakan teknik studi kepustakaan, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa odcast Husein Ja’far berhasil menjadi media dakwah digital yang efektif untuk menyampaikan pesan toleransi beragama. Selain itu Penggunaan platform digital yang akrab dengan Generasi Z, seperti YouTube, mendukung penyebaran nilai-nilai Islam yang inklusif. Metode penyampaian yang digunakan bersifat santai namun bermakna, sehingga menarik perhatian pendengar muda. Penelitian ini diharapkan dapat menjadi referensi bagi pelaku dakwah agar pendekatan dakwah yang lebih menarik dan sesuai dengan kebutuhan remaja dalam meningkatkan kesadaran dan partisipasi keagamaan.